2020
DOI: 10.4209/aaqr.2020.05.0225
|View full text |Cite
|
Sign up to set email alerts
|

Impact of SARS-CoV-2 on Ambient Air Particulate Matter in Tehran

Abstract: The pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has indirectly produced both positive and negative effects on the environment, particularly in terms of air quality. Our study aimed to determine these effects in the city of Tehran by comparing the ambient PM 2.5 and PM 10 levels recorded at 22 air quality monitoring stations during the outbreak (20 February-2 April 2020) with those from the corresponding period last year (20 February-3 April 2019). Contrary to expectation, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 19 publications
2
34
0
Order By: Relevance
“…A study conducted in Iran (Broomandi et al, 2020) highlighted that unfavourable meteorological conditions as a combination of reduced rainfall and relative humidity and increased temperature can hinder pollutant dispersion increasing the aerosol optical depth in the atmosphere during lockdown. This result agrees with the observations performed in Tehran by Faridi et al (2020) that reported higher concentrations of both PM2.5 (20.5 %) and PM10 (16.5 %) during lockdown.…”
Section: Accepted Manuscriptsupporting
confidence: 93%
“…A study conducted in Iran (Broomandi et al, 2020) highlighted that unfavourable meteorological conditions as a combination of reduced rainfall and relative humidity and increased temperature can hinder pollutant dispersion increasing the aerosol optical depth in the atmosphere during lockdown. This result agrees with the observations performed in Tehran by Faridi et al (2020) that reported higher concentrations of both PM2.5 (20.5 %) and PM10 (16.5 %) during lockdown.…”
Section: Accepted Manuscriptsupporting
confidence: 93%
“…In concordance with the observed findings, a 10% reduction in the average level of particulate matter pollution was observed during the one month of lockdown in Europe (CREA, 2020), while in Barcelona (Spain) the reduction of PM 10 varied from 28 to 31% (Tobias et al, 2020). However, during COVID-19 pandemic due to excess use of private vehicles in Iran to avoid the social contact resulted in worsening of the ambient particulate matter quality (Faridi et al, 2020). The significant reduction (p < 0.05) in the mean concentration of NO 2 was observed in all the four cities, with highest reduction noticed in Mumbai (74.4%).…”
Section: Resultsmentioning
confidence: 92%
“…The emission of greenhouse gases and the air pollutants have decreased considerably due to the enforcement of protective quarantine, specifically closures of shopping centers and factories, limitations on transportation, and travel all over the world [32,33]. In contrast, recent research in Tehran narrated an upsurge in the concentrations of PM 10 and PM 2.5 owing to an increase in the usage of private cars during the quarantine [34]. Studies performed in various territories of China have demonstrated that stringent COVID-19 control strategies substantially decreased intensities of certain toxins excluding ozone [35,36].…”
Section: Resultsmentioning
confidence: 99%